God's Holy Spirit: a back-story from the Joseph narrative (Genesis 37-50) - Barbara Green (Acta Theologica)
The story of Judah within the longer Joseph story (Genesis 37-50) provides an apt place for readers to discern the work of the Holy Spirit and what is recognized in spirituality as the work of discernment. The character goes from venal and crass to empathetic and self-giving, and the question is how the narrative shows evidence of that process. With the help of the philosopher/theorist Mikhail Bakhtin, the narrated experience of the character in seven scenes is examined for evidence of Judah’s journey of transformation – presumably guided by God’s widening and inspiring Spirit, with special attention given to the scene (Genesis 44) where Judah must persuade his (unrecognized) brother Joseph, serving as Viceroy of Egypt, to allow Judah to take punishment in place of their brother Benjamin for the sake of their father. The larger Holy Spirit and discernment context of the story is the dreams of Joseph.